Family Support Education for Hypertension Patients: A Case Study of Blood Pressure Reduction - Rossyana Septiasih; Swito Prastiwi; Eko Sari Wahyuni (Health Gate, 2026)
Lack of family support in patients with hypertension is often influenced by family perceptions and limited knowledge regarding hypertension management. This condition may lead to inadequate attention to patients and poor adherence to treatment and preventive measures. In contrast, family attention, empathy, and involvement in patient care can positively influence patient behavior and improve psychological well-being. This study aimed to identify the level of family support among patients with hypertension before and after the implementation of family support education. This research employed a descriptive case study design involving two research subjects. Data were collected using a family support questionnaire covering emotional, informational, instrumental, and appraisal support. The findings showed that before the educational intervention, subject 1 had not met family support in all four aspects, with informational support being the lowest due to limited access to health information. Meanwhile, subject 2 showed the lowest score in instrumental support due to economic limitations. After the implementation of family support education, both subjects demonstrated improvements and fulfilled all four aspects of family support. It is recommended that families maintain these four aspects of support to enhance patient care, and future researchers are encouraged to conduct separate assessments between family members and patients to obtain more comprehensive results.